Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am stuck on doing this implicit differentiation problem below. $$y \cos x = 4x^2 + 3y^2$$

I am now stuck at the following equality and I don't know how to proceed. Can someone help me? $$y(−\sin x) + (\cos x)y' = 8x + 6yy' $$

share|cite|improve this question
What does the problem ask you to do? If you're trying to solve for $y'$ in terms of $x$ and $y$, try getting both $y'$ terms on one side of the equation and factoring. – Jonas Meyer Jun 29 '12 at 20:36
Yeah im trying to find $y'$ – soniccool Jun 29 '12 at 20:37
@soniccool Is it clear how you get $$y(− \sin x) + \cos x · y' = 8x + 6yy' $$ from $$y \cos x = 4x^2 + 3y^2?$$ – user17762 Jun 29 '12 at 20:38
up vote 1 down vote accepted

Group the $y'$ terms to one side to get $$(\cos(x)-6y)y' = 8x + y \sin(x) \implies y' = \dfrac{8x + y \sin(x)}{\cos(x) - 6y}$$

share|cite|improve this answer

What Marvis noted can be formulated below. Let $F(x,y)=0$ is a relation linking two variables $x$, $y$ implicitly. Then you can find $y'$ from this relation by calculating $$y'=\frac{-F_x}{F_y}$$ where in $F_x$ is differentiate of $F$ with respect to $x$. Now, $y \cos x = 4x^2 + 3y^2$ becames $y \cos x - 4x^2 - 3y^2=0$. Take $F(x,y)=y \cos x - 4x^2 - 3y^2=0$ and the rest is as Marvis did completely.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.